(untitled) (Sains Humanika, 2017)
This article reviewed past studies that were carried out in the past decades (2002-2015) on the linkage between supervisory support and training transfer. Most of the organizations have invested billions of dollars onto training. However, training transfer is still in unsatisfactory status. Supervisory support is recognized as one of the aspect that could have an effect on training transfer. However, the importance of supervisory support in training transfer has been overlooked in the past studies. Thus, this paper intends to highlight the needs to make further investigations on the linkage between these two variables. Some suggestions were provided for future studies.Â Â